Effect of planting methods and tillage practices on soil health and maize productivity - Gao, Peng Ju; Abbas, Hasnain; Li, Fa Qiao; Tang, Guo Rong; Lv, Ju Zhi; Zhou, Xun Bo (Frontiers in Plant Science, 2024)
To increase the crop yield, the amount of agrochemicals used in field has increased in recent years. Moreover, indiscriminate use of chemical fertilizers has led to soil deterioration and compaction. Inclusion of straw and tillage practices to the field could play an important role in improving the soil quality and crop yield. Therefore, we hypothesized that combination of straw return and different tillage practices would result in improvement in soil health and crop productivity. Therefore an experiment was conducted a split plot design during 2018-2022. They were comprised of traditional planting with no straw return and straw return, accompanied by four different tillage methods: control (no tillage), rotary tillage (25 cm tillage depth), subsoiling (35 cm tillage depth), and subsoiling plus rotary tillage (35+25 cm tillage depth). Results showed that subsoiling along with rotary tillage enhanced soil total nitrogen (TN) by 9.0%, soil organic carbon (SOC) 7.5%, soil microbial biomass carbon (MBC) 6.8%, soil catalase (S-CAT) 9.6 %, soil urease (S-UE) 4.1%, soil cellulase (S-CL) 14.5%, soil sucrase (S-SC) 10.8% and maize yield 3.0% compared to no tillage. Correlation analysis showed that (i) maize yield was significantly and positively correlated with S-SC, S-CL, S-UE, SOC, and TN. (ii) S-SC was significantly and positively correlated with TN, SOC, and MBC. (iii) TN was significantly and positively correlated with S-UE, and SOC was significantly and positively correlated with S-SC. It has been concluded that straw return coupled with subsoiling and rotary tillage is an appropriate approach to enrich soil nutrients, enzyme activities, and maize yield.